A metal bar cutting scrap collecting and briquetting device
Patent Information
- Application Number
- CN202511184265.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-22
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-08-22
AI Technical Summary
[0004]但是,对于现有的压块机来说,其输送排出的圆柱状的压实块,仍然存在表面掉渣的情况,并且其表面较为粗糙,相邻的压实块在运输过程中容易发生碰撞,这些都会加剧掉渣;另外,压实块表面由于没有防护,在通过人工捡拾时,必须佩戴劳保手套,由于切割碎屑即使经过压缩,也很容易侵蚀劳保手套,对劳保手套的损伤大,严重时,甚至导致工人手部出现过渡刺激带来的不适
[0015]所述金属棒料切割碎屑收集压块装置能够将金属棒料切割时所产生的碎屑收集并压实成圆柱形压实块,压实块的圆周面表面被涂胶形成胶膜,形成结构致密的固化膜,能最大限度降低压实块在后续转移过程掉渣,同时,由于固化膜的存在,即使光手接触该压实块,也不容易出现扎手、过敏等现象,安全性高。
Smart Images

Figure CN121018238B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cutting equipment technology, specifically a metal bar cutting debris collection and briquetting device. Background Technology
[0002] In the field of metal bar cutting, a large amount of smoke and dust, as well as cutting debris, are generated. To deal with these smoke and dust, a negative pressure adsorption tube is usually installed at the head of the cutting machine. After adsorption, the smoke and dust are separated by a cyclone separator. The separated cutting debris is then briquetting using a briquetting machine.
[0003] Compacted blocks obtained by compacting metal bar cutting chips generally do not require the use of binders mixed into the metal bar cutting chips. The volume of the formed compacted blocks is reduced to 1 / 3 to 1 / 5 of the volume of the metal bar cutting chips used, which facilitates storage and transportation and reduces losses during transportation and smelting in the recycling process.
[0004] However, for existing briquetting machines, the cylindrical compacted blocks they discharge still have surface flaking, and their surfaces are relatively rough. Adjacent compacted blocks are prone to collisions during transportation, which exacerbates flaking. In addition, since the surface of the compacted blocks is unprotected, workers must wear protective gloves when picking them up manually. Even after compression, the cutting debris can easily corrode the protective gloves, causing significant damage. In severe cases, it can even lead to discomfort caused by excessive stimulation to the workers' hands.
[0005] Based on this, the present invention is proposed. Summary of the Invention
[0006] This invention addresses the shortcomings of existing technologies by providing a metal bar cutting debris collection and briquetting device, the technical solution of which is as follows:
[0007] A metal bar cutting debris collection and briquetting device includes a debris suction pipe, a cyclone separator, a briquetting machine, and a collection box. The briquetting machine has a feed pipe at its top, which is connected to the discharge valve of the cyclone separator. The debris suction pipe is connected to the air inlet of the cyclone separator. Metal bar cutting debris is compacted into cylindrical briquettes by the briquetting machine through the debris suction pipe and the cyclone separator. A glue-coating conveying pipe is provided between the briquetting machine and the collection box. The compacted briquettes output by the briquetting machine are conveyed to the collection box through the glue-coating conveying pipe. During the process of passing through the glue-coating conveying pipe, the cylindrical surface of the compacted briquettes is first coated with glue, and then curing begins.
[0008] As a further embodiment of the present invention, the adhesive-coated conveying pipe includes a pipe body, the first end of which is connected to a briquetting machine, and the tail end of which is integrally connected to a tapered pipe section. An outer pipe body is integrally connected to the tapered pipe section and fitted over the outer pipe body. A steel wire ring is disposed inside the outer pipe body, and two annular springs are fitted around the steel wire ring. An arc-shaped upper piezoelectric ceramic plate and an arc-shaped lower piezoelectric ceramic plate are disposed between the steel wire ring and the outer pipe body. Both the upper and lower piezoelectric ceramic plates are fixedly connected to the outer pipe body. The annular springs are connected to both the upper and lower piezoelectric ceramic plates. The steel wire ring is detachably connected to the annular springs. A water storage chamber is formed between the tapered pipe section, the pipe body, and the steel wire ring. A water pipe connected to the water storage chamber is disposed outside the tapered pipe section.
[0009] As a further embodiment of the present invention, the head of the tube is provided with an adhesive application hole arranged along the circumference of the tube, and the head of the tube is fitted with an annular groove, and the annular groove and the tube form an adhesive storage cavity that communicates with all the adhesive application holes.
[0010] As a further aspect of the present invention, the ratio of the arc length of the lower piezoelectric ceramic sheet to the arc length of the upper piezoelectric ceramic sheet is 1.7.
[0011] As a further aspect of the present invention, water is injected into the water storage chamber through a water pipe at a flow rate of 60-80 ml / min; the resonant frequency of the lower piezoelectric ceramic plate is 1.2 kHz, and the resonant frequency of the upper piezoelectric ceramic plate is 215 kHz.
[0012] As a further embodiment of the present invention, a metering pump is provided outside the annular groove. The metering pump pumps the sluggish 502 glue into the glue storage chamber and applies glue to the compacted block passing through the glue application hole.
[0013] As a further embodiment of the present invention, the desensitizing 502 glue is prepared by mixing 502 glue and 1,2-diacetic acid glycerol in a mass ratio of 10:3.
[0014] Compared with the prior art, the beneficial effects of the present invention are:
[0015] The metal bar cutting debris collection and compaction device can collect and compact the debris generated during metal bar cutting into cylindrical compacted blocks. The circumferential surface of the compacted block is coated with adhesive to form an adhesive film, which forms a dense and solidified film. This can minimize the shedding of debris during the subsequent transfer process. At the same time, due to the presence of the solidified film, even if you touch the compacted block with bare hands, it is not easy to experience sharp hands, allergies, or other problems, thus ensuring high safety. Attached Figure Description
[0016] Figure 1 A schematic diagram of a device for collecting and compressing metal bar cutting debris;
[0017] Figure 2 This is a schematic diagram of the adhesive-coated delivery pipe.
[0018] Figure 3 This is a schematic diagram of the interior of the outer tube.
[0019] Figure 4 These are photos of the compacted block after the surface curing film has cured.
[0020] Figure 5 This is a photograph of an existing compacted block without adhesive coating on its surface. Detailed Implementation
[0021] The present invention will be described in detail below with reference to specific embodiments. These embodiments are merely some, not all, implementations of the present invention. All other implementations obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0022] Example 1
[0023] like Figure 1 As shown, a metal bar cutting debris collection and briquetting device includes a debris suction pipe, a cyclone separator, a briquetting machine 20, and a collection box 50. The top of the briquetting machine 20 is equipped with a feed pipe 21, which is connected to the discharge valve of the cyclone separator. The debris suction pipe is connected to the air inlet of the cyclone separator. Metal bar cutting debris is compacted into cylindrical briquettes by the briquetting machine 20 through the debris suction pipe and the cyclone separator. A glue-coating conveying pipe 30 is provided between the briquetting machine 20 and the collection box 50. The compacted briquettes output by the briquetting machine 20 are conveyed to the collection box 50 through the glue-coating conveying pipe 30. During the process of the compacted briquettes passing through the glue-coating conveying pipe 30, the cylindrical surface of the compacted briquettes is first coated with glue, and then curing begins.
[0024] Ultimately, after the adhesive on the surface of the compacted block cures, it forms a dense adhesive film. On the one hand, this minimizes the possibility of the compacted block surface crumbling again; on the other hand, it also minimizes the corrosion of work gloves.
[0025] In this invention, adhesive can be applied to the cylindrical surface of the compacted block through simple equipment modifications, thus meeting practical application requirements. It is unnecessary to apply adhesive to both ends of the compacted block; doing so would make the equipment extremely complex, reducing its practical value, and the ends of the compacted block are also rarely used surfaces.
[0026] Example 2
[0027] like Figure 2 , 3As shown, the adhesive-coated conveying pipe 30 includes a pipe body 31. The first end of the pipe body 31 is connected to the briquetting machine 20. The tail end of the pipe body 31 is integrally connected to a tapered pipe section 33. The tapered pipe section 33 is integrally connected to an outer pipe body 331, which is sleeved on the outside of the pipe body 31. A steel wire ring 36 is provided inside the outer pipe body 331. Two annular springs 37 are sleeved on the outside of the steel wire ring 36. An arc-shaped upper piezoelectric ceramic plate 3 is provided between the steel wire ring 36 and the outer pipe body 331. 8. An arc-shaped lower piezoelectric ceramic plate 35; both the upper piezoelectric ceramic plate 38 and the lower piezoelectric ceramic plate 35 are fixedly connected to the outer tube body 331; all annular springs 37 are connected to the upper piezoelectric ceramic plate 38 and the lower piezoelectric ceramic plate 35; the steel wire ring 36 is detachably connected to the annular spring 37; a water storage chamber 34 is formed between the tapered tube section 33, the tube body 31, and the steel wire ring 36; a water pipe 40 connected to the water storage chamber 34 is provided outside the tapered tube section 33.
[0028] The head of the tube 31 is provided with an adhesive application hole 311 arranged around the circumference of the tube 31. The head of the tube 31 is covered with an annular groove 32, and the annular groove 32 and the tube 31 form an adhesive storage cavity that communicates with all the adhesive application holes 311.
[0029] The ratio of the arc length of the lower piezoelectric ceramic sheet 35 to the arc length of the upper piezoelectric ceramic sheet 38 is 1.7.
[0030] Water is injected into the water storage chamber 34 through the water pipe 40 at a flow rate of 60-80 ml / min; the resonant frequency of the lower piezoelectric ceramic plate 35 is 1.2 kHz, and the resonant frequency of the upper piezoelectric ceramic plate 38 is 215 kHz.
[0031] A metering pump is installed outside the annular groove 32. The metering pump pumps the sluggish 502 glue into the glue storage chamber and applies glue to the compacted block passing through the glue application hole 311.
[0032] The desensitizing 502 glue is prepared by mixing 502 glue and 1,2-diacetol in a mass ratio of 10:3. 1,2-diacetol has the molecular formula C7H. 12 O5, CAS number 102-62-5.
[0033] In this invention, the existing curing mechanism of 502 glue is:
[0034] The curing process of 502 glue relies on the reaction of cyanoacrylate with moisture in the air or on the surface of the object. When the glue is squeezed out of the bottle, it quickly comes into contact with water vapor in the air or moisture on the surface of the object, triggering a polymerization reaction to form a strong polymer, thereby quickly bonding the objects together. However, the curing time is also affected by the thickness of the glue film and the humidity of the air. The initial curing time of existing 502 glue is usually 1-5 minutes, such as the stainless steel / metal 502 glue purchased from Yeyong (Dongguan) New Material Technology Co., Ltd. Therefore, in the application environment of this invention, if the curing time of the 502 glue is too fast, it may be applied online. In this invention, the 502 glue is temporarily stored in the glue storage chamber, where it is almost not in contact with moisture, so the 502 glue in the glue storage chamber will basically not cure; and because the 502 glue continuously flows out of the glue application hole 311, it is generally not easy to cure at the glue application hole 311 either; and even if there is slight curing and soft gel, it will be worn away during the continuous entry and exit of the compaction block.
[0035] In this invention, the curing time of 502 glue at 20°C and 65±5% relative humidity is 3.6 min; however, the curing time of the desensitive 502 glue, due to the addition of 1,2-diacetic acid glycerol, is extended to 9.1 min under the same test conditions. If glycerol is used instead of 1,2-diacetic acid glycerol, with other conditions remaining unchanged, the corresponding control glue (relative to the desensitive 502 glue) has a curing time of 4.7 min.
[0036] Because the curing time of the 502 glue is extended, and the interval between two adjacent compacted blocks falling into the collection box 50 generally does not exceed 30 seconds, the 502 glue needs to cure to a certain extent within 30 seconds; otherwise, the two contacting compacted blocks may easily stick together. To avoid this, water is injected into the water storage chamber 34, causing the lower piezoelectric ceramic plate 35 and the upper piezoelectric ceramic plate 38 to vibrate, which in turn causes the annular spring 37 and the steel wire ring 36 to generate a certain degree of rhythm. The steel wire ring 36 is made of stainless steel wire randomly wound into a circular structure; thus, a layer of water film is evenly applied to the surface of the compacted block that has been coated with glue at the point where the steel wire ring 36 passes, thereby accelerating the curing of the slow-curing 502 glue and shortening its curing time to less than 22 seconds. The annular spring 37 is used to connect the steel wire ring 36 by binding, minimizing the contact between the steel wire ring 36 and the surface of the compacted block, and minimizing the impact on the glue film on the surface of the compacted block. If water pressure is used alone for spraying, it is easy to overspray, which will cause the cured film formed after the adhesive has cured to become a porous and brittle structure. Therefore, it is necessary to use the lower piezoelectric ceramic sheet 35 and the upper piezoelectric ceramic sheet 38 in conjunction with vibration.
[0037] Figure 4 This is a picture of a compacted block after the surface curing film has cured. Figure 5 It is an existing compacted block whose surface is not coated with adhesive and is prone to crumbling.
[0038] Characterization test of surface spalling of compacted blocks
[0039] Experiment 1: A compacted block with a diameter of 5cm and a length of 8cm was placed on a test slope with an angle of 60° and a length of 1cm and rolled naturally downwards. At the bottom of the test slope, a row of 10 round iron balls with a diameter of 3cm was placed, and the compacted block collided with the round iron balls. The collision was repeated 3 times, and the resulting debris was collected and weighed. The mass of the collision debris was obtained. The larger the mass of the collision debris, the worse the protective effect of the cured film. The collision debris mainly comes from two sources: some residual cured adhesive on both ends of the compacted block provides a certain degree of protection, but the vibration generated by the main collision also causes debris to fall off; another source is the partial detachment of the cured film, which also causes some debris to fall off.
[0040] Experiment 2: Following the method of Experiment 1, repeat the collision 10 times and record the number of cured film detached pieces (area greater than 2mm × 2mm) on the surface of the compacted block. In this invention, due to the use of a large amount of water for catalytic curing, the cured film is relatively brittle. Therefore, after a large number of collisions, local detachment is likely to occur. The larger the number of cured film detached pieces, the worse the bonding between the cured film and the surface of the compacted block, as well as the worse the properties of the cured film.
[0041] The experimental results are shown in Table 1:
[0042] Table 1
[0043] This invention 3.7 4 Uncoated compacted blocks 47.1 / Reference example 1 1.9 2 Comparative Example 1 23.2 27 Comparative Example 2 14.9 19 Comparative Example 6 20.8 9 Comparative Example 7 32.3 23
[0044] Reference example 1
[0045] In this example, 502 glue was applied manually to the surface of the compacted block using a brush and allowed to dry naturally.
[0046] As shown in Table 1, this method is the best, but it is very inefficient and cannot be applied on a large scale. The purpose of this invention is to be as close as possible to Reference Example 1.
[0047] Compare with Example 1
[0048] In this example, ethanol is used instead of 1,2-diacetic acid glycerol, and the rest is the same as in Example 2.
[0049] Compare with Example 2
[0050] In this example, glycerol is used instead of 1,2-diacetic acid glycerol, and the rest is the same as in Example 2.
[0051] As shown in Table 1, although ethanol and glycerol, which also act as diluents, can delay the curing time of 502 glue, the addition of large amounts of ethanol and glycerol will seriously affect the quality of the subsequently cured film.
[0052] Compare with Example 3
[0053] In this example, the ratio of the arc length of the lower piezoelectric ceramic sheet 35 to the arc length of the upper piezoelectric ceramic sheet 38 is 1, while the rest remain unchanged. This results in the cured film on the surface of the compacted block being very soft; after a light rub by hand, the cured film completely disappears. The reason may be that the 502 glue was soaked in too much water, preventing the cured film from completely curing.
[0054] Compare with Example 4
[0055] In this example, the ratio of the arc length of the upper piezoelectric ceramic sheet 38 to the arc length of the lower piezoelectric ceramic sheet 35 is 1.7, with the rest remaining unchanged. This results in the cured film on the surface of the compacted block becoming very brittle and powdery. The cured film cracks and is easily removed by hand after a light rub. The reason may be that the water overflowing from the wire ring 36 exceeds the amount required for curing, resulting in partial curing but incomplete curing.
[0056] As can be seen from the above, the effective range of the upper piezoelectric ceramic plate 38 and the lower piezoelectric ceramic plate 35 mainly affects the degree of water overflow at the steel wire ring 36. After a large number of experiments, it is preferred that the ratio of the arc length of the lower piezoelectric ceramic plate 35 to the arc length of the upper piezoelectric ceramic plate 38 is 1.7.
[0057] Compare with Example 5
[0058] In this example, instead of using piezoelectric ceramic sheets 38 and 35, a ring-shaped piezoelectric ceramic block is used. When its resonant frequency is 1.2kHz, a uniform cured film cannot form on the surface of the compacted block, and a large amount of glue will clog the wire ring 36; the wire ring 36 becomes clogged after 3 hours of continuous operation. Furthermore, if the resonant frequency of the piezoelectric ceramic block is 215kHz, clogging occurs after only 5 minutes of operation.
[0059] Compare with Example 6
[0060] In this example, the resonant frequency of the lower piezoelectric ceramic sheet 35 is 215kHz, and the resonant frequency of the upper piezoelectric ceramic sheet 38 is 1.2kHz; the rest are the same as in Example 2.
[0061] Compare with Example 7
[0062] In this example, the resonant frequency of the lower piezoelectric ceramic sheet 35 is 1.2 kHz, and the resonant frequency of the upper piezoelectric ceramic sheet 38 is 1.2 kHz; the rest are the same as in Example 2.
[0063] Compare with Example 8
[0064] In this example, the resonant frequency of the lower piezoelectric ceramic plate 35 is 215kHz, and the resonant frequency of the upper piezoelectric ceramic plate 38 is 215kHz; all other parameters are the same as in Example 2. During the experiment, it was found that the steel wire coil 36 needed to be replaced after 5 hours of continuous operation due to a certain degree of blockage.
[0065] In Example 2, the wire ring 36 only needs to be replaced after 31 hours of continuous operation.
[0066] As can be seen from the above, the resonant frequencies of the lower piezoelectric ceramic sheet 35 and the upper piezoelectric ceramic sheet 38 mainly affect the degree of vibration dispersion of the fluid (such as water or glue) near the steel wire ring 36. While avoiding compressing the steel wire ring 36 into a compacted block, it is also necessary to promote the formation of a uniformly distributed water film near the steel wire ring 36. Excessive vibration may cause the steel wire ring 36 to compress the block, while insufficient vibration will result in an uneven water film, thus affecting the curing of the 502 glue. After extensive testing, the resonant frequency of the lower piezoelectric ceramic sheet 35 is 1.2 kHz, and the resonant frequency of the upper piezoelectric ceramic sheet 38 is 215 kHz.
[0067] Furthermore, it should be understood that those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.
Claims
1. A metal bar cutting debris collection and briquetting device, comprising a debris suction pipe, a cyclone separator, a briquetting machine (20), and a collection box (50), wherein the top of the briquetting machine (20) is provided with a feed pipe (21), the feed pipe (21) is connected to the discharge valve of the cyclone separator, the debris suction pipe is connected to the air inlet of the cyclone separator, and the metal bar cutting debris is compacted into cylindrical compacted blocks by the briquetting machine (20) through the debris suction pipe and the cyclone separator; characterized in that: A glue-coating conveying pipe (30) is provided between the briquetting machine (20) and the collection box (50). The compacted blocks output by the briquetting machine (20) are conveyed to the collection box (50) through the glue-coating conveying pipe (30). During the process of the compacted blocks passing through the glue-coating conveying pipe (30), the cylindrical surface of the compacted blocks is first coated with glue and then begins to solidify. The adhesive-coated conveying pipe (30) includes a pipe body (31), the first end of which is connected to a briquetting machine (20), and the tail end of which is integrally connected to a tapered pipe section (33). The tapered pipe section (33) is integrally connected to an outer pipe body (331), which is fitted over the pipe body (31). A steel wire ring (36) is provided inside the outer pipe body (331), and two annular springs (37) are fitted around the outside of the steel wire ring (36). An arc-shaped upper piezoelectric ceramic plate (38) is provided between the steel wire ring (36) and the outer pipe body (331). An arc-shaped lower piezoelectric ceramic plate (35) is provided. The upper piezoelectric ceramic plate (38) and the lower piezoelectric ceramic plate (35) are both fixedly connected to the outer tube body (331). The ring springs (37) are all connected to the upper piezoelectric ceramic plate (38) and the ring springs (37) are all connected to the lower piezoelectric ceramic plate (35). The steel wire ring (36) is detachably connected to the ring spring (37). A water storage chamber (34) is formed between the tapered tube section (33), the tube body (31) and the steel wire ring (36). A water pipe (40) connected to the water storage chamber (34) is provided outside the tapered tube section (33).
2. The metal bar cutting debris collection and briquetting device according to claim 1, characterized in that: The head of the tube (31) is provided with a glue-applying hole (311) arranged around the circumference of the tube (31), and the head of the tube (31) is covered with an annular groove (32). The annular groove (32) and the tube (31) form a glue storage cavity that communicates with all the glue-applying holes (311).
3. The metal bar cutting debris collection and briquetting device according to claim 1, characterized in that: The ratio of the arc length of the lower piezoelectric ceramic sheet (35) to the arc length of the upper piezoelectric ceramic sheet (38) is 1.
7.
4. The metal bar cutting debris collection and briquetting device according to claim 3, characterized in that: Water is injected into the water storage chamber (34) through the water pipe (40), with a water flow rate of 60~80ml / min; the resonant frequency of the lower piezoelectric ceramic plate (35) is 1.2kHz, and the resonant frequency of the upper piezoelectric ceramic plate (38) is 215kHz.
5. The metal bar cutting debris collection and briquetting device according to claim 2, characterized in that: A metering pump is installed outside the annular groove (32). The metering pump pumps the sluggish 502 glue into the glue storage chamber and applies glue to the compacted block passing through the glue application hole (311) through the glue application hole (311).
6. The metal bar cutting debris collection and briquetting device according to claim 5, characterized in that: The desensitizing 502 glue is made by mixing 502 glue and 1,2-diacetic acid glycerol in a mass ratio of 10:3.
Citation Information
Patent Citations
Metal bar cutting scrap cleaning device
CN222154834U
Debris Collection Device for Cutting Mechanism and LCD Panel Cutting Debris Suction Device
US20130104336A1